CALCULATION OF CHARACTERISTICS OF STIFFNESS AND ELASTICITY OF RAIL THREADS WHEN TORSION UNDER COMBINED ACTION OF VERTICAL AND HORIZONTAL FORCES - Danilenko, E. I. (Science and Transport Progress, 2016)
Purpose. Reference data in technical literature about such characteristics as stiffness and elasticity of rail threads at torsion are rather contradictory. This is due to the absence of correct analytical solution of this task and because of complexity of experimental studies of this problem under combined action of vertical and horizontal lateral forces. The article presents the new method of solving the task of calculation the real values of stiffness and elasticity modules of rail thread when torsion under combined action of vertical and horizontal lateral forces. Methodology. The complex method of solving the problem was used in the paper. It includes the theoretical part and the results of the experiment. Using the experiment the characteristics of horizontal lateral stiffness of the rail threads of the head and bottom at different constructions of the modern rail fastenings was measured. The second task of determination of the real values of elasticity and stiffness modulus of the rail thread when torsion was solved by the theoretical methods. Findings. New values of stiffness characteristics and elasticity module of rail thread when torsion for the modern rail constrictions Р65, UIC60, Р50 and the rail fastenings of the types КПП, КБ, ДО, under combined action of vertical and horizontal forces and torsion were obtained. Originality. For the first time in domestic research it was carried out the experimental and theoretical solution of the task for determination of the real values of the stiffness and elasticity modulus of rail thread when torsion under combined action of vertical and horizontal forces of the wheel loadings. The solution is represented in the functional dependence on the correlation of vertical and horizontal forces ; acting together. The solution is carried out for the modern designs of the rails of domestic standard P65, P50, P43 and international standard UIC60. Practical value. The obtained results make it possible to carry out calculations of the real acting strains and deformations in the rails of different types under the joint action of vertical and horizontal forces for railway track on concrete and wooden sleepers with different designs of rigid and elastic rail fastenings КБ, КПП, Д0 with higher accuracy as compared to the current calculation methodology.